Field induced spontaneous quasiparticle decay and renormalization of quasiparticle dispersion in a quantum antiferromagnet - Tao Hong (Nature Portfolio, 2017)
Spontaneous magnon decay in canted antiferromagnets has been theoretically investigated extensively, but experimental evidence is limited. Here the authors study the spin ½ antiferromagnet DLCB via neutron scattering, revealing field-induced spontaneous magnon decay associated with three-magnon interactions.